2011
DOI: 10.1002/pat.1548
|View full text |Cite
|
Sign up to set email alerts
|

Star‐like polyfluorenes based on 2,4,6,8, 10,12‐hexabenzyl‐2,4,6,8,10,12‐hexaazaisowurtzitane caged‐core: toward non‐aggregating, blue‐light‐emitting polymers

Abstract: Multi‐functionality compound 2,4,6,8,10,12‐hexa(p‐bromo)‐benzyl‐2,4,6,8,10,12‐hexaazaiso‐wurtzitane (Br‐HBIW) was synthesized and used for the core of star‐like polymers. Star‐like polyfluorene based on 2,4,6,8,10,12‐hexabenzyl‐2,4,6,8,10,12‐hexaazaisowurtzitane (HBIW) caged‐core was synthesized by Suzuki coupling method. The comparative studies between the star‐like polyfluorene and the linear polyfluorene based on UV–Vis and photoluminescence (PL) spectra revealed that the bulky HBIW cage could reduce the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The photophysical and electronic properties of various p-conjugated oligomers and polymers sensitively depend on their conformations and packing structures in condensed phases (solutions, films, and amorphous solids). For example, it has been demonstrated that oligothiophene ( n T, n = 6) aggregates exhibited a blue-shift in absorption spectra relative to the isolated molecule, probably due to the increase in the twisted structures and the decrease in the effective conjugation length (ECL). On the contrary, most polyfluorenes (PFs), which are famous for their strong luminescence and facile color-tuning via structural modifications, were observed to undergo a small red-shift about 1–18 nm in absorption spectra of films relative to those of solutions. How do you explain the different trends in spectra shifts upon aggregation for n Ts and PFs? This work aims to present a general picture for understanding the (red or blue) shift in adsorption spectra from the (increasing or reducing) contents of planar-conjugated conformations through a systematic study on the absorption spectra of PFs.…”
Section: Introductionmentioning
confidence: 99%
“…The photophysical and electronic properties of various p-conjugated oligomers and polymers sensitively depend on their conformations and packing structures in condensed phases (solutions, films, and amorphous solids). For example, it has been demonstrated that oligothiophene ( n T, n = 6) aggregates exhibited a blue-shift in absorption spectra relative to the isolated molecule, probably due to the increase in the twisted structures and the decrease in the effective conjugation length (ECL). On the contrary, most polyfluorenes (PFs), which are famous for their strong luminescence and facile color-tuning via structural modifications, were observed to undergo a small red-shift about 1–18 nm in absorption spectra of films relative to those of solutions. How do you explain the different trends in spectra shifts upon aggregation for n Ts and PFs? This work aims to present a general picture for understanding the (red or blue) shift in adsorption spectra from the (increasing or reducing) contents of planar-conjugated conformations through a systematic study on the absorption spectra of PFs.…”
Section: Introductionmentioning
confidence: 99%